APPROACHES TO THE FORMATION OF RECREATIONAL CULTURE IN THE STUDENT ENVIRONMENT (Physical Culture and Sport: Scientific Perspective, 2024)
This article examines approaches to forming a recreational culture in the student environment and its benefits. The role of recreational culture in the life of student youth, its impact on comprehensive development, and student welfare are characterized. The authors focus on the importance of creating favorable conditions for the development of recreational culture in educational institutions, particularly through providing appropriate infrastructure, organizing events, and motivational support for students.An author's definition of "recreational culture" is provided, which is considered as an integrated system of accepted behavioral models, acquired experience, and forms of activity aimed at satisfying the physical, spiritual, and social needs of individuals during their leisure time through events and activities in the field of health and recreation.In this study, we conducted an analysis of sociological, culturological, psychological, and adaptive approaches to the study of recreational culture. We found that these approaches help understand the impact of recreational activities on personal well-being, social interactions, and health, as well as assess the effectiveness of various strategies for managing recreational resources. It is highlighted that a comprehensive approach to research, encompassing different scientific disciplines, is key to a deeper understanding of recreational culture.It is noted that the key directions for forming a recreational culture among student youth include integrating various types of physical activity to engage students in regular physical exercises; developing motivation and independence in choosing types of physical activity; involving modern technologies, such as fitness apps, online training, and virtual sports competitions for youth.The article also highlights the prospects for further explorations in this direction, which include integrating technologies, interdisciplinary research, social inclusion, ecological sustainability, globalization, psychological aspects, economic impact, and the development of educational programs.
Keywords: recreation; physical activity; recreational culture; approaches; student youth